On the paleoichthyofauna from the Aiuruoca Tertiary Basin, Minas Gerais State, Brazil (Ameghiniana, 2013)
Abstract. A new fish fauna from the Tertiary Aiuruoca Basin is presented in a preliminar overview. This recently reported basin is located in southern Minas Gerais State, between the Mantiqueira Mountain Range and the south border of the Minduri Range, in the Alto Rio Grande Plateau. The Aiuruoca Basin is filled up by sediments of two formations: Entre-Córregos (lacustrine) and Pinheirinho (alluvial fan). The shales of the Entre-Córregos Formation are dated as Eocene-Oligocene based on palynomorphs. Its fossil content also includes plants, insects, amphibians and fishes. In a preliminar examination the paleoichthyofauna includes cichlids (Teleostei, Perciformes) and characids (Teleostei, Characiformes), most of them complete and articulated. Members of these groups are primary freshwater fishes corroborating the continental paleoenvironment assigned to this formation. First studies have demonstrated a close similarity between these fish species and those from the Taubaté Basin. Resumen. PALEOICTIOFAUNA DE LA CUENCA DE AIURUOCA (TERCIARIO), ESTADO DE MINAS GERAIS, BRASIL. En este trabajo se presenta un estudio preliminar de los peces fósiles de la cuenca terciaria de Aiuruoca, ubicada entre la Sierra da Mantiqueira y el borde sur de la Sierra de Minduri en el planalto del Alto Rio Grande, al sur del Estado de Minas Gerais. La cuenca de Aiuruoca está constituida por sedimentos de las formaciones Entre-Córregos (facies lacustres) y Pinheirinho (abanicos aluviales). Las lutitas de la Formación Entre-Córregos están datadas como Eoceno-Oligoceno en base a palinomorfos. Su contenido fosilífero incluye además plantas, insectos, peces y anfibios. La paleoictiofauna está formada principalmente por cíclidos (Teleostei, Perciformes) y carácidos (Teleostei, Characiformes), representados en su mayoría por ejemplares completos y articulados. Los representantes de estos dos grupos son peces esencialmente de agua dulce, corroborando el ambiente lacustre atribuido a esta formación. Resultados preliminares revelan una gran semejanza entre los peces de las cuencas cenozoicas de Aiuruoca y Taubaté.